Fiscal policy and learning - Kaushik Mitra; George W. Evans; Seppo Honkapohja (Bank of Finland, 2012)
Using the standard real business cycle model with lump-sum taxes, we analyze the impact of fiscal policy when agents form expectations using adaptive learning rather than rational expectations (RE). The output multipliers for government purchases are significantly higher under learning, and fall within empirical bounds reported in the literature (in sharp contrast to the implausibly low values under RE). Effectiveness of fiscal policy is demonstrated during times of economic stress like the recent Great Recession. Finally it is shown how learning can lead to dynamics empirically documented during episodes of "fiscal consolidations."
URN:NBN:fi:bof-20140807316
Keywords: E62; D84; E21; E43; 330; Government Purchases; Expectations; Output Multiplier; Fiscal Consolidation; Taxation